Strategies for structural adjustment : the experience of Southeast Asia: papers presented at a seminar held in Kuala Lumpur, Malaysia, June 28-July 1,1989 (International Monetary Fund ; Bank Negara Malaysia, 1990)
This collection of papers delivered at a seminar, moderated by Ungku A. Aziz, in Kuala Lumpur addresses issues of economic and structural adjustment and trade and exchange rate policies in Southeast Asia.